University Students' Dishonest Academic Practices: The Case of the College of Basic Education in Kuwait - Al Suwaileh, Bader; Al-Radaan, Dalal (جامعة عين شمس - كلية التربية, 2015)
هدفت هذه الدراسة الى التعرف على مدى شيوع الممارسات غير المقبولة أكاديميا لطلاب وطالبات كلية التربية الاساسية بدولة الكويت. كما هدفت ايضا الى فحص ما إذا كانت هناك فروق دالة احصائيا في مدى شيوع هذه الممارسات بين الذكور والاناث. أيضا، تم اختبار درجة الارتباط بين مدى شيوع الممارسات غير المقبولة أكاديميا والمستوى الاكاديمي للطلاب والطالبات. وتم اشتقاق خمس عشرة ممارسة غير مقبولة أكاديميا من الدراسات ذات الصلة. واشات نتائج التحليل الاحصائي للاستبيان الذي طبق على عينة عشوائية عنقودية تكونت من 1109 طالبا وطالبة الى: 1.شيوع الممارسات غير المقبولة أكاديميا بين طلاب وطالبات كلية التربية الاساسية. 2.شيوع الممارسات غير المقبولة أكاديميا بين الطالبات أكثر من الطلاب. 3.عدم وجود ارتباط دال احصائيا بين المستوى الاكاديمي للطلاب والطالبات ومدى شيوع الممارسات غير المقبولة أكاديميا.
This study aimed to examine the extent to which academic dishonesty is common among undergraduate students’ at the College of Basic Education. It also sought to compare the frequency of such practices among male and female undergraduates. Furthermore, this study examined the correlation between students’ perceptions of academic dishonesty and their grade point average (GPA). Fifteen potential dishonest academic practices were derived from the related literature. A questionnaire survey was administered to a sample of 1,109 male and female undergraduate students who were chosen using cluster-sampling method. The results indicated that: 1. The dishonest academic practices are common at College of Basic Education. 2. Female students exercise higher levels of academic dishonesty in comparison with their male counterparts. 3. There is no statistical correlation between students’ perceptions of academic dishonesty and their GPA.
Keywords: الممارسات الخاطئة -- طلاب الجامعات -- كلية التربية الاساسية -- الكويت